2014
DOI: 10.1371/journal.pone.0092351
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Esophageal Squamous Cell Carcinoma by Cathepsin B Activity in Nude Mice

Abstract: Background and ObjectiveDespite great progress in treatment, the prognosis for patients with esophageal squamous cell carcinoma (ESCC) remains poor, highlighting the importance of early detection. Although upper endoscopy can be used for the screening of esophagus, it has limited sensitivity for early stage disease. Thus, development of new diagnosis approach to improve diagnostic capabilities for early detection of ESCC is an important need. The aim of this study was to assess the feasibility of using catheps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“… 22 Moreover, CTSB was highly upregulated in human esophageal squamous cell carcinoma (ESCC), suggesting it plays a key role in the regulation of ESCC initiation and progression. 23 , 24 In the present study, we observed a significant increase of CTSB levels in the sera of patients with esophageal cancer compared with that of the healthy controls. Furthermore, CTSB levels were positively correlated with increasing tumor invasion depth, which is consistent with the findings listed earlier.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“… 22 Moreover, CTSB was highly upregulated in human esophageal squamous cell carcinoma (ESCC), suggesting it plays a key role in the regulation of ESCC initiation and progression. 23 , 24 In the present study, we observed a significant increase of CTSB levels in the sera of patients with esophageal cancer compared with that of the healthy controls. Furthermore, CTSB levels were positively correlated with increasing tumor invasion depth, which is consistent with the findings listed earlier.…”
Section: Discussionsupporting
confidence: 63%
“…Tan et al showed that the serum level of CTSB was considerably higher in nasopharyngeal carcinoma patients than in controls and was correlated with the TNM score 22. Moreover, CTSB was highly upregulated in human esophageal squamous cell carcinoma (ESCC), suggesting it plays a key role in the regulation of ESCC initiation and progression 23,24. In the present study, we observed a significant increase of CTSB levels in the sera of patients with esophageal cancer compared with that of the healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Cathepsin B is a potential target for detecting esophageal cancer [ 60 ] because it is expressed at low levels in the normal esophageal mucosa but is significantly overexpressed in esophageal cancer [ 61 ]. Habibollahi et al used white-light upper endoscopy combined with near-infrared imaging to detect cathepsin B and thereby screen for esophageal adenocarcinoma [ 62 ].…”
Section: Esophageal Cancermentioning
confidence: 99%
“…Herein, we established a novel, noninvasive, miRNA-based signature using a systematic and comprehensive effort and by integrating transcriptomewide biomarker discovery and clinical validations using 7 independent, retrospective and prospective, multinational, multicenter cohorts. Our 8-miRNA signature demonstrated considerable clinical value for the noninvasive detection of early stage ESCC patients, remarkably superior to conventional tumor biomarkers for ESCC [17]. Application of our circulating, epigenetic signature as a non-invasive, inexpensive and facile diagnostic assay for ESCC could improve the mortality of patients with ESCC, long considered one of the deadliest malignancies.…”
Section: Introductionmentioning
confidence: 92%